2011
DOI: 10.1007/s11060-011-0633-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrating functional MRI information into conventional 3D radiotherapy planning of CNS tumors. Is it worth it?

Abstract: The purpose of our study was to examine the potential benefits of integrating functional MRI (fMRI) information into the 3D-based planning process for central nervous system (CNS) malignancies. Between 01.01.2008 and 01.12.2009, ten patients with astrocytoma (both low and high-grade histological type) were enrolled in this study. Before the planning process, conventional CT planning, postoperative MR, and individual functional MRI examinations were conducted. For the functional MRI examination four types of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Work has also looked at the robustness of this technique in terms of recommending planning margins of uncertainty ( 11 ). The benefits of including such information remain to be proven, but results show that several primary functional areas can be included in the planning prescription without any adverse changes to the planning target volume (PTV) coverage ( 12 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Work has also looked at the robustness of this technique in terms of recommending planning margins of uncertainty ( 11 ). The benefits of including such information remain to be proven, but results show that several primary functional areas can be included in the planning prescription without any adverse changes to the planning target volume (PTV) coverage ( 12 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the integration of fMRI, in terms of activations or RSNs, into radiotherapy (RT) treatment planning is not done and this literature is limited [ 14 16 ]. Furthermore, there is a lack of literature on the longitudinal effects after the surgery and during RT [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that with fMRI based 3D conformal planning, radiotherapy dose to the superior and inferior temporal gyrus and lingual gyrus could be reduced by an average of 50%. A subsequent study of 10 patients with brain tumours confirmed the role of fMRI in reducing dose to critical organs without compromising tumour target coverage (90).…”
Section: The Potential For Integrating Modern Imaging With Novel Radimentioning
confidence: 86%